Experimental Investigation on the Flow Resistance of a Staged Fuel Injector with Thermal Protection. (31st March 2021) - Zhang, Jingyu; Wang, Xinyi; Wu, Yu; He, Xiaomin
Abstract : The multistaged rotating swirling usually adopts the staged combustion and multiple point fuel supply, which has the advantages of high efficiency and low emissions. However, the high inlet temperature rise will cause autooxidation and fuel coking. Multiple fuel circuit mutual cooling technology by using different flight conditions is an effective measure for the thermal protection of the nozzle. But the complicated fuel circuit configuration inevitably increase the flow resistance in the fuel jet. This paper presents an experimental investigation of flow resistance of a triple-stage rotating swirling nozzle, concerning the effects of various factors on total pressure loss and friction factor in nozzle fuel circuit. The factors include fuel velocity V f, i, inlet temperature T f, i, and inlet Reynolds number Re f, i . The results show that the complicated fuel-cooled structure made flow resistance of the pilot fuel circuit much bigger than the main one. Meanwhile, the empirical correlations between the friction factor and the inlet Reynolds number have been fitted, which can be the reference for engineering design.